2015
DOI: 10.1016/j.techfore.2014.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of patent citations in biotechnology: An analysis of patent influence across the industrial and organizational boundaries

Abstract: The present paper extends the literature investigating key drivers leading certain patents to exert a stronger influence on the subsequent technological developments (inventions) than other ones. We investigated six key determinants, as (i) the use of scientific knowledge, (ii) the breadth of the technological base, (iii) the existence of collaboration in patent development, (iv) the number of claims, (v) the scope, and (vi) the novelty, and how the effect of these determinants varies when patent influence-as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(60 citation statements)
references
References 101 publications
2
53
0
Order By: Relevance
“…Consistently, previous studies revealed that the number of claims is positively related with the probability of patent litigation (Lanjouw and Schankerman 2001;Su, Chen, and Lee 2012). Therefore, having a high number of claims may positively impact the value of the patent (Gambardella, Harhoff, and Verspagen 2008;Lee et al 2007;Messeni Petruzzelli, Rotolo, and Albino 2015) and its attractiveness within MFTs. Nevertheless, this positive influence may decrease after a certain threshold.…”
Section: Claimssupporting
confidence: 82%
See 3 more Smart Citations
“…Consistently, previous studies revealed that the number of claims is positively related with the probability of patent litigation (Lanjouw and Schankerman 2001;Su, Chen, and Lee 2012). Therefore, having a high number of claims may positively impact the value of the patent (Gambardella, Harhoff, and Verspagen 2008;Lee et al 2007;Messeni Petruzzelli, Rotolo, and Albino 2015) and its attractiveness within MFTs. Nevertheless, this positive influence may decrease after a certain threshold.…”
Section: Claimssupporting
confidence: 82%
“…Differently, patents with a broader scope may be more likely to be developed by internal R&D departments, consistently with an organisation's long-term strategy. Patents characterised by a Downloaded by [University of Nebraska, Lincoln] at 23:37 05 April 2015 4 A. Messeni Petruzzelli et al broader scope may in fact result from specific firms' strategic decisions (Merges and Nelson 1990), thus making them less valuable for other organisations (Messeni Petruzzelli, Rotolo, and Albino 2015). Accordingly, we posit that: Hypothesis 1.…”
Section: Scopementioning
confidence: 91%
See 2 more Smart Citations
“…Kang and Park [13] examined the influence of government R&D support and inter-firm collaborations on innovation in 147 Korean biotechnology companies using patent and survey data. In addition to these innovation studies, Petruzzelli et al [14] clarified the determinants of patent citations in biological technology, focusing on patent influence using data for 293 U.S. biotechnology companies from 1976 to 2003.…”
Section: Literature Reviewmentioning
confidence: 99%